2015
DOI: 10.1007/s10151-015-1284-7
|View full text |Cite
|
Sign up to set email alerts
|

The OTSC® proctology clip system for the closure of refractory anal fistulas

Abstract: The novel OTSC(®) proctology system is a safe and effective method for the closure of even complex and recurrent fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 12 publications
0
32
0
1
Order By: Relevance
“…In a small retrospective study of 10 patients with refractory anal fistulas, including 6 patients with perianal CD, the procedure was technically successful in all patients and permanent fistula closure was achieved in 7/10 (70 %) within a median time for healing of 72 days 86. Its long-term efficacy remains to be investigated.…”
Section: The Role Of Endoscopy In the Management Of Perianal Fistulasmentioning
confidence: 99%
“…In a small retrospective study of 10 patients with refractory anal fistulas, including 6 patients with perianal CD, the procedure was technically successful in all patients and permanent fistula closure was achieved in 7/10 (70 %) within a median time for healing of 72 days 86. Its long-term efficacy remains to be investigated.…”
Section: The Role Of Endoscopy In the Management Of Perianal Fistulasmentioning
confidence: 99%
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…A single case series68 reported the use of OTSC ® in anal fistula. Of the ten patients treated, six had fistula associated with Crohn's disease.…”
Section: Resultsmentioning
confidence: 99%
“…En 3 de los 7 pacientes con cierre de la fístula, se pudo retirar el clip posteriormente. 31 9) Estoma derivativo. Proctectomía En 2016 se publicó un estudio prospectivo en el que se analizaron los resultados tras realizar un estoma derivativo indicado por afectación colónica o perianal de la enfermedad de Crohn 32 .…”
Section: ) Over-the-scope-clip (Otsc)unclassified